PENGATURAN PENEMPATAN NARAPIDANA TRANSGENDER YANG BELUM MEMILIKI SURAT PUTUSAN BERGANTI KELAMIN DARI PENGADILAN DI DALAM LEMBAGA PEMASYARAKATAN INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Correctional Institutions have become a public spotlight, since the reformation of the bureaucratic reform in the Ministry of Law and Human Rights itself, problems are often found in prisons. The problem of regulating transgender placement for which there has been no decision to change sex from the Court within the Indonesian Penitentiary. Indonesia currently has no regulation on Prison for a transgender person. To avoid unwanted things, such as verbal, physical, or sexual harassment while undergoing legal proceedings in a correctional institution.Formulation of the problem of writing this thesis, first. How is the implementation of the punishment for the placement of transgender prisoners who do not have a gender-change court decision in a correctional facility. Second, what is the legal problem in the placement of transgender prisoners who do not have a gender-change court decision in a correctional facility. Third, what are the arrangements related to the placement of transgender prisoners who do not have a gender change decision from the court in the correctional institution for the future. The purpose of writing this thesis, namely; First, in order to know the implementation of the punishment for placing transgender prisoners who do not have a gender-change court decision in a correctional facility. Second, in order to know the legal problem of the absence of regulations related to the placement of transgender prisoners against victims and perpetrators. Third, it is necessary to know the arrangements related to the placement of transgender prisoners who do not yet have a gender change decision from the court in the correctional institution for the future. The type of research used in this legal research is the normative juridical method. This type of research is the principles of law. This research is descriptive, because the author describes the principles of law, namely the principle of equality before the law.Keywords: Prisoners-Transgender-Penitentiary